The importance of trust for electronic commerce satisfaction: an entrepreneurial perspective - Shirazi F.; Adam N.A.; Shanmugam M.; Schultz C.D. (Emerald Group Holdings Ltd., 2023)
article; electronic commerce; food industry; human; least square analysis; satisfaction; social media; structural equation modeling; theoretical study; trust